Dancing with Change: A Conceptual Analysis of How Family Businesses Embrace Product Development Management - Nyayu Lathifah Tirdasari; Wawan Dhewanto; Neneng Nurlaela Arief (Research Synergy Foundation, 2024)
Understanding product development management is crucial, particularly within the context of family businesses, which are renowned for their resistance to change. Family firms demonstrate a paradox in innovation: while inclined toward calculated risk-taking, they often invest less in R&D compared with non-family businesses. This article explores the evolving landscape of product development management literature related to family businesses. It achieves this by meticulously examining pertinent scholarly works. Conducting a systematic review focused on family businesses’ product development management practices. This article poses the following fundamental question: What prior research has delved into the intersection of family businesses and product development management? The authors adopted the updated Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) reporting guidelines to ensure transparency and completeness in their systematic literature review. The research process hinges on accessing academic databases housing peer-reviewed journals, which initially yielded 955 articles. Through a series of discerning study selection phases, this number was pruned down to 68 articles eligible for further assessment. Ultimately, this study incorporates insights from 22 articles. Within the domain of product development management, the responsibility is typically divided among three key parties: marketing, design, and manufacturing. Notably, the findings underscore a predominant emphasis on the marketing perspective in the existing literature. Consequently, this article calls for future research endeavors to delve into the roles of design and manufacturing in the context of family business and product development management.